Erectile dysfunction and sexual quality of life in patients who underwent low‐dose‐rate brachytherapy alone for prostate cancer. (24th October 2021) - Nakai, Yasushi; Tanaka, Nobumichi; Asakawa, Isao; Miyake, Makito; Anai, Satoshi; Yamaki, Kaori; Hasegawa, Masatoshi; Fujimoto, Kiyohide
Summary: This study evaluated erectile function and sexual quality of life (QoL), and predictive factors for erectile dysfunction (ED) and the deterioration of sexual QoL in 70 patients who underwent low‐dose‐rate brachytherapy (LDR‐BT) alone for prostate cancer without androgen deprivation therapy. Erectile function and sexual QoL were evaluated before and 1, 3, 6, 12, 24, 36, 48 and 60 months after LDR‐BT. Binary logistic regression analysis was used to determine whether age, prostate volume, hypertension, diabetes, Brinkman's index, testosterone, baseline Sexual Health Inventory for Men (SHIM) score and post‐implant dosimetry parameters could predict ED and deterioration of sexual QoL at 24 and 60 months after LDR‐BT. After 24 and 60 months, ED was noted in 39 of 70 patients and 42 of 64 patients respectively. Furthermore, sexual QoL worsened in 42 of 70 and 43 of 64 patients respectively. Baseline SHIM score was identified as a significant predictor of ED (24 months: odds ratio [OR]: 0.83, p = 0.02; 60 months: OR: 0.83, p = 0.03) and the deterioration of sexual QoL (24 months: OR: 0.84, p = 0.03). LDR‐BT for prostate cancer promoted decreased erectile function and sexual QoL, with high preimplant potency being a significant predictor of ED and the deterioration of sexual QoL.